1987
DOI: 10.1017/s0001566000006139
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Changes in Birth Seasonality of Twins During 1971–1984 in Japan

Abstract: Birth dates of 1,536 twin-pairs in 1971-1984 were collected from the members of an association of twins' mothers. The seasonal variation of twinning changed every 2-4 years. Years when twinning rate was higher in the summer-fall season (1971-72, 1976-77, 1982-84) and those when a peak of the rate was not observed (1973-75, 1978-81) appeared alternately. In years with a summer-fall peak, the elevation of twinning in the summer-fall season was detected consistently in both like- and unlike-sexed and in both MZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…However, when observed each year, this seasonality was not always found, there being some exceptional years such as 1979, 1980, and 1993. This instability may be consistent with the intermittent appearance of seasonality in twinning reported by Nakamura et al (1987). The present results suggest that there is a basic tendency for multiple ovulation to occur more in October-March, which roughly corresponds to births in July-December.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, when observed each year, this seasonality was not always found, there being some exceptional years such as 1979, 1980, and 1993. This instability may be consistent with the intermittent appearance of seasonality in twinning reported by Nakamura et al (1987). The present results suggest that there is a basic tendency for multiple ovulation to occur more in October-March, which roughly corresponds to births in July-December.…”
Section: Discussionsupporting
confidence: 89%
“…Imaizumi et al (1980) reported seasonality in the twinning rate in Japan in 1974 through a nationwide survey, noting that there was an elevation in April for both MZ and DZ twin births. Nakamura et al (1987) analyzed data from a Japanese association for the mothers of twins, and found evidence suggesting variation in the seasonality of twinning: no apparent seasonality in some consecutive years and elevation in summerto-fall months in other consecutive years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 -Association (OR) of concordant-sex, discordant-sex, and all twin birth events with conception during March-August, by type of analysis Analysis Crude analysis 1 Matched analysis 2 Logistic regression (unconditional) 13 Logistic regression (conditional) [2][3] All n = 2336 OR (95% C.I. )…”
Section: Resultsmentioning
confidence: 99%
“…Although there exists strong support for an inherited susceptibility to twinning [4,14], there are reasons to believe that environmental factors play a role as well. Among the latter are several studies demonstrating cyclic variations in twin births within geographi-cally defined populations [6][7][8]13,[15][16][17]. One interpretation of such patterns is that they reflect changes in ambient luminosity and subsequent promotion of multiple ovulations in women who are genetically predisposed to twinning [1,2,9,12].…”
Section: Introductionmentioning
confidence: 99%